Graphene Oxide‐Assisted Multiple Cross‐Linking of MXene for Large‐Area, High‐Strength, Oxidation‐Resistant, and Multifunctional Films. (30th December 2022) - Li, Bin; Wu, Na; Yang, Yunfei; Pan, Fei; Wang, Changxian; Wang, Gang; Xiao, Long; Liu, Wei; Liu, Jiurong; Zeng, Zhihui
Abstract: Transition metal carbides/nitrides (MXenes) with metallic electrical conductivity and excellent processability attract increasing attention for assembling multifunctional macrostructures. However, the challenges, involving poor mechanical strength, inferior oxidation stability, and limited scalable manufacturing, impede their wide applications. Herein, the large‐area, high‐strength, ultra‐flexible hybrid films are developed through the multiple physical and chemical cross‐linking of MXene/cellulose films facilitated by graphene oxide. The MXene‐based films manifest significantly improved hydrophobicity, water/solvent resistance, and oxidation stability, and meanwhile, maintain excellent conductivity and electromagnetic interference shielding performance. The X‐band surface‐specific shielding effectiveness (SE) of 18, 837.5 dB cm 2  g −1 and an SE over 60 dB in an ultra‐broadband frequency range are achieved, comparable to the best shields ever reported. Furthermore, the wearable films demonstrate excellent photothermal antibacterial and electrothermal deicing applications. Thus, such high‐performance MXene‐based films developed through a facile and scalable manufacturing method have substantial application prospects in flexible electronics, thermotherapy, electromagnetic compatibility, and aerospace. Abstract : Flexible, high‐strength, oxidation‐resistant, and large‐area MXene‐based films of multiple cross‐linking facilitated by graphene oxide are prepared by a facile, sustainable, and scalable approach. The MXene‐based composite films exhibit excellent hydrophobicity, water resistance, and electrical conductivity, as well as remarkable and stable EMI shielding, photo‐/electrothermal, photothermal antibacterial, and electrothermal deicing performance.